Influence of cytochrome P450 (CYP) 2C8 polymorphisms on the efficacy and tolerability of artesunate‐amodiaquine treatment of uncomplicated Plasmodium falciparum malaria in Zanzibar - Pernaute-Lau, Leyre (2022)
Funding Information: Open Access funding provided by Karolinska Institute. The work was funded by the Swedish Research Council [Grant ref. VR-2014-3134] and the Erling-Persson Family Foundation [Grant ref. 4-3031/2018]. L.P.L. is recipient of a fellowship from BioSys PhD programme PD65-2012 (Ref SFRH/BD/142860/2018) from Fundação para a Ciência e Tecnologia (Portugal). Publisher Copyright: © 2021, The Author(s).